2020
DOI: 10.1038/s41598-020-71099-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis complex infection in Asian elephants (Elephas maximus) using an interferon gamma release assay in a captive elephant herd

Abstract: Tuberculosis is highly contagious disease that can be transmitted between humans and animals. Asian elephants ( Elephas maximus ) in captivity live in close contact with humans in many Asian countries. In this study, we developed an interferon gamma release assay (IGRA) for elephant TB detection using antigens from the MTB complex (MTBC) and nontuberculous mycobacteria (NTM) as stimulating antigens (PPD, ESAT6, CFP10) to elicit a cell-mediated immune response (CMIR). The developed assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…We found that 33 (21.56%) elephants were seropositive using the ElephantTB Stat-Pak® Assay. Similar seropositive rates have been reported in captive elephants in Malaysia 15.87% (10/63) [24], Thailand 30% (18/60) [35], and Laos 36% (29/80) [12].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that 33 (21.56%) elephants were seropositive using the ElephantTB Stat-Pak® Assay. Similar seropositive rates have been reported in captive elephants in Malaysia 15.87% (10/63) [24], Thailand 30% (18/60) [35], and Laos 36% (29/80) [12].…”
Section: Discussionsupporting
confidence: 84%
“…Asian elephants are mainly reported to be affected and the majority of cases are due to Mycobacterium tuberculosis, a causative agent of human TB [19,22]. Culture-confirmed cases and TB seroprevalence rates in captive elephants have been reported from several Asian elephant range countries: Nepal [20,[25][26][27], Thailand [2][3]35], India [36], Malaysia [24], and Laos [12]. TB has also been reported in captive elephants from USA [22][23], Australia [37], Sweden [13], and Japan [39], suggesting a worldwide distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The infection prevalence of M. bovis based on culture of ororespiratory samples (OS and BAL) was 4%, which was significantly lower than the estimated prevalence based on IGRA (79.1%) in this population. This discrepancy could be due to a predominant cellmediated immune response in early infection (without shedding) or in animals that have cleared infection, similar to other species (van der Heijden et al, 2020;O'Halloran et al, 2018;Songthammanuphap et al, 2020). It is also possible that IGRA-positive wild dogs that may be containing or clearing infection are less likely to shed M. bovis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the tuberculin skin test is not sufficiently sensitive in elephants 16 . Interferon-gamma release assay (IGRA), a recent standard test in humans, has not yet been practical in elephants although there have been some attempts to develop it 17 19 . A rapid immuno-test kit, Dual Path Platform (DPP) VetTB assay for elephants (Chembio Diagnostic Systems, Medford, NY), is used worldwide for elephant TB screening 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%